(untitled) (ELT-Lectura, 2016)
The Purpose of this research was to find out students’ ability in reading texts in Test of English for the Foreign Language (TOEFL) at English Education Department of Lancang Kuning University. Design of this research was survey design. Sample of the research was 23 students at the Seventh semester Students of English Education Department of Lancang Kuning University. The researcher used test as instrument that was reading texts in TOEFL in term of multiple choice. Test was analyzed by using ‘descriptive statistics’. The result of analyzing data showed that the students’ scores was 1214, mode was 46, median was 52, variance was 157.35 and standard deviation was 12.54. Mean was 52.78 Thus, researcher concluded that students’ ability in reading texts in TOEFL was categorized into weak